Euro crash the exit route from monetary failure in Europe - Brown, Brendan 1951- (Palgrave Macmillan, 2012)
Euro Crash diagnoses the three fatal design flaws in EMU as constructed by the Maastricht Treaty and analyses future likely monetary scenarios for Europe, demonstrating how the best of these would be the creation of a new narrow monetary union between France and Germany founded on strict monetarist principle and without a European Central Bank.